2020
DOI: 10.1187/cbe.19-10-0197
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Religious Backgrounds and Evolution Acceptance of Black and Hispanic Biology Students

Abstract: An evolution education study spanning 77 courses and 17 states found that Black and Hispanic students’ stronger than average religiosity explains their lower evolution acceptance. This indicates a need to take into account students’ religious culture and background to teach evolution in an inclusive way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
(168 reference statements)
0
26
0
1
Order By: Relevance
“…In this study, we also found that Muslim students and Christian students who were not Catholic had the highest perceived conflict with their belief in God and evolution, which suggests that these students could benefit the most from reducing their perceived conflict. Non-Catholic Christian students are approximately one-quarter of introductory undergraduate biology students (Barnes et al, 2020b), suggesting that reducing perceived conflict among this group could impact a sizable proportion of undergraduate biology students and their acceptance of evolution. These results corroborate past studies demonstrating that Muslim individuals may experience high perceived conflict with their religions and evolution (Dagher and BouJaoude, 1997;BouJaoude et al, 2011;Deniz et al, 2008;Yousuf et al, 2011;Asghar, 2013;Athanasiou and Papadopoulou, 2015;Yok et al, 2015;Stears et al, 2016;Rachmatullah et al, 2018;Unsworth and Voas, 2018;Barnes et al, under review).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we also found that Muslim students and Christian students who were not Catholic had the highest perceived conflict with their belief in God and evolution, which suggests that these students could benefit the most from reducing their perceived conflict. Non-Catholic Christian students are approximately one-quarter of introductory undergraduate biology students (Barnes et al, 2020b), suggesting that reducing perceived conflict among this group could impact a sizable proportion of undergraduate biology students and their acceptance of evolution. These results corroborate past studies demonstrating that Muslim individuals may experience high perceived conflict with their religions and evolution (Dagher and BouJaoude, 1997;BouJaoude et al, 2011;Deniz et al, 2008;Yousuf et al, 2011;Asghar, 2013;Athanasiou and Papadopoulou, 2015;Yok et al, 2015;Stears et al, 2016;Rachmatullah et al, 2018;Unsworth and Voas, 2018;Barnes et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that Muslim students and Christian students who were not Catholic had the highest perceived conflict with their belief in God and evolution, which suggests that these students could benefit the most from reducing their perceived conflict. Non-Catholic Christian students are approximately one-quarter of introductory undergraduate biology students ( Barnes et al. , 2020b ), suggesting that reducing perceived conflict among this group could impact a sizable proportion of undergraduate biology students and their acceptance of evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What evidence do these discussions provide about the progression of students’ evolutionary reasoning? What is the instructional experience of students who are members of groups that are underrepresented in evolutionary science ( Mead et al , 2015 ; Barnes et al ., 2020 )?…”
Section: Discussionmentioning
confidence: 99%